The Andhra Forests - Khan, A. A. (Indian Forester, 1954)
The Andhra forests extend over a total area of 13,172 sq. miles. The two main types met with are the dry-deciduous and the dry-evergreen. The ex-panchayat and the ex-zamindari forests which have been taken over by the Forest Department are in a most degraded state and strenuous efforts are being made to rehabilitate them by modern methods of silviculture.